Viral zoom: COVID-19 as multi-scalar immune failure. Issue 3 (1st September 2020) - Horton, Zachary
ABSTRACT: This essay argues that COVID-19 has functioned as a zoom, or a device that both discursively and materially articulates a wide range of scales together as a strategic continuity. This scalar continuity then structures both knowledge and experience through its lens. Applying 'scalar difference theory' to the coronavirus crisis of 2020, this essay explores the biopolitical, medial, and narrative dynamics that enabled the virus to disrupt and hijack the multi-scalar systems that were meant to contain it. COVID-19's scalar politics are tracked as scalar operations, stabilized scalar milieus, and elided scalar difference, and contextualized both historically and ecologically. While COVID-19 has been popularly narrativized as an exogenous threat posed by a viral agent, this essay argues for a multi-scalar understanding of COVID-19 as a general condition of human empire in the Anthropocene, an auto-immune response from within.